Wine and music (III): so what if music influences the taste of the wine?. Issue 1 (December 2015) - Spence, Charles; Wang, Qian
Abstract A growing body of evidence, both anecdotal and scientifically rigorous, now points to the fact that what people taste when evaluating a wine, not to mention how much they enjoy the experience, can be influenced by the specifics of any music that happens to be playing at the same time. The question that we wish to address here is 'So what?' Why should anyone care that music (or, for that matter, specially composed soundscapes) exert(s) a crossmodal influence over the wine-tasting experience? 'Why not just drink great wine and forget about the music?' a sceptic might ask. Here, we outline a number of the uses that such research findings have been put to in the marketplace, in experiential events, in artistic performances, and in terms of furthering our theoretical understanding of those factors that influence the tasting experience. We also highlight how the latest in technology (think sensory apps and hyperdirectional loudspeakers, not to mention digitally augmented glassware) augurs well for those wanting to deliver the most stimulating, the most memorable, and certainly the most multisensory of tasting experiences in the years to come. Demonstrations of sound's influence on wine perception will most likely be applicable to a variety of other drinks and foods too. Ultimately, the argument is forwarded that there are many reasons, both theoretical and applied, as to why we should all care about the fact that what we listen to can change the sensory-discriminative, the descriptive, and the hedonic attributes of what we taste.